Controlled Synthesis of Pnicogen-Chalcogen Polycations in Ionic Liquids - Groh, Matthias F.; Isaeva, Anna; Mueller, Ulrike; Gebauer, Paul; Knies, Maximilian; Ruck, Michael (European Journal of Inorganic Chemistry, 2016)
Three new pnicogen-chalcogen polycations were synthesized under specific conditions in the Lewis-acidic ionic liquids (ILs) [EMIm]X·nAlX3 and [BMIm]X·nAlX3 (X = Cl, Br; [EMIm]: 1-ethyl-3-methylimidazolium, [BMIm]: 1-butyl-3-methylimidazolium) and crystallized as their tetrahalogenidoaluminate salts. Single-crystal X-ray diffraction revealed the new polycation [Bi6Te4Br2]4+ in triclinic [Bi6Te4Br2](AlBr4)4 as the reaction product of bismuth, tellurium, and bismuth tribromide. Substitution of the elements with Bi2Te3 yielded the heterocubane [Bi4Te4]4+ in tetragonal [Bi4Te4](AlBr4)4, which crystallizes isotypically to its known chlorine counterpart. The latter is also accessible from ILs. The interactions between cations and anions were evaluated by quantum-chemical calculations. Bi2S3, which is insoluble in most media, readily dissolves in the employed IL and forms the new augmented heterocubane [Bi3S4AlCl]3+, which crystallizes with the complex anion [S(AlCl3)3]2- as triclinic [Bi3S4AlCl][S(AlCl3)3]AlCl4. Quantum-chemical calculations support the assignment of elements in this compound. The monoclinic crystal structure of [Sb13Se16](AlCl4)6(Al2Cl7) contains a new member of the small family of pnicogen-chalcogen spiro-heterocubanes.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Chalcogens; Heterocubanes; Ionic liquids; Pnicogens; Polycations